Miconia portogallensis (Melastomataceae) a new species from the Sierra Madre del Sur, Guerrero, Mexico - de Santiago Gómez, Jesús Ricardo; Michelangeli, Fabián A. (Phytotaxa, 2016)
Miconia portogallensis, a new dioecious species of Miconia section Cremanium from the Sierra Madre del Sur of Guerrero (Mexico), is described and illustrated. Its relationships and similarities with M. oligotricha and other Mexican species of section Cremanium are discussed. A key to dioecious species of Miconia in Mexico and Mesoamerica is provided.